Condition of a grassland from east of Chaco (Semiárida, 2020)
The aim of this study was to assess the condition of a grassland of Eastern Chaco. The work was done on a livestock ranch in Makalle (Chaco). Vegetation is characterized by herbaceous plants dominated by warm season grasses. Proportion of preferred, intermediate and undesirable species was determined, based on their forage attributes. Quantity of annuals and weed species, percent bare soil, vigour of best species and dry matter yield (Kg DM/ha) were also determined. The grassland had 40.4% preferred species with good vigour, low percentage of weeds (2%) and low bare soil (2%). Dry matter yield was 1639.1 kg DM/ha (seasonal mean). Condition was rated good to excellent. No deterioration was detected.
Keywords: Grassland; condition